Robustness improvement of actively controlled structures through integrated structural/control design - Rao, S. S.; Pan, T. S.; Wright Laboratory (Wright-Patterson Air Force Base, Ohio); Purdue University. (Fliight Dynamics Directorate, Wright Laboratory, Air Force Systems Command, 1991)
The problem of structural and control design of flexible structures is considered. Three major topics are investigated. The first topic deals with the dual passive/active control design for flexible structures. The interacting sub-structure decentralized control approach is developed for large flexible structures to eliminate the spillover problem and reduce the model size for controller margin and robustness of controlled flexible structures. The second topic considers the robustness improvement for controlled flexible structures through structure modifications. The stability and engineering performance robustness indices are defined. The integrated structural/control design problem is considered as a multiobjective optimization problem in which three objectives- structural weight, stability robustness index and performance robustness index- are considered for minimization. The third topic involves the study of the actuator/sensor location selection problem. The sequential-best-adding, penalty function method and the genetic algorithm are considered.
"Final Report for Period October 1987 - May 1991."
"May 1991."
Includes bibliographical references (pages 152-162).
The problem of structural and control design of flexible structures is considered. Three major topics are investigated. The first topic deals with the dual passive/active control design for flexible structures. The interacting sub-structure decentralized control approach is developed for large flexible structures to eliminate the spillover problem and reduce the model size for controller margin and robustness of controlled flexible structures. The second topic considers the robustness improvement for controlled flexible structures through structure modifications. The stability and engineering performance robustness indices are defined. The integrated structural/control design problem is considered as a multiobjective optimization problem in which three objectives- structural weight, stability robustness index and performance robustness index- are considered for minimization. The third topic involves the study of the actuator/sensor location selection problem. The sequential-best-adding, penalty function method and the genetic algorithm are considered.
Research supported by the United States Air Force Flight Dynamics Directorate, and performed by School of Mechanical Engineering, Purdue University, West Lafayette, Indiana, under Contract No.F33615-87-C-3256
Keywords: Space vehicles / Control systems.; Space vehicles / Design and construction.